Level of knowledge of pregnant women in the public service about humanized birth - Santos, Amanda Basílio Bastos dos; Melo, Enaldo Vieira de; Dias, Júlia Maria de Gonçalves; Didou, Rayssa da Nóbrega; Araujo, Rodrigo Almeida Santiago de; Santos, Willas de Oliveira; Araújo, Lorena Barreto (ABCS Health Sciences, 2019)
Introduction: The awareness of pregnant women is fundamental to positive birth experiences. Objective: To analyze the level of knowledge on humanized birth of pregnant women from two public services and characterize the sample epidemiologically. Methods: Descriptive study using questionnaire between June and August 2017. Sample with 297 pregnant women being selected 200 after applying the exclusion criteria. Association test of variables were used (Chi-square and Fisher’s exact test). Results: Mean age was 26.6 years. Majority were from countryside (72.5%), income up to a minimum wage (90.5%) and more of eight years of education (62.5%). 71% started prenatal care in the first trimester and it was conducted by physician in 71% of cases. 71% preferred vaginal delivery and 44% related fear of cesarean. Prenatal professional in charge did not provide information for 66.5%. 30.5% have heard about humanized childbirth, among these, 83.6% showed adequate concepts. Associations were observed between prior knowledge of humanized childbirth and origin (Aracaju) (p=0.03), higher income (p 0.02), lower abortion incidence (p=0.04), prenatal physician (p=0.04) and preference for normal childbirth (p=0.04). Among women without previous knowledge on humanized childbirth there association of correct concept with higher income (p=0.03), schooling (p=0.02) and prenatal physician (p=0.01) Conclusion: The majority did not know about humanized delivery, were from the countryside with lower income, preference for normal birth, were not informed on the types of delivery by the professional practitioner (in majority doctors), whom knew properly. Adequate concepts about humanized childbirth, even in the absence of prior information, were associated to socio-economic and prenatal variables.